THE DIFFERENCES IN NUTRITIONAL STATUS OF CHILDREN OF WORKING MOTHERS WITH AREN’T WORKING IN THEKEJOBONG DISTRICT PURBALINGGA REGENCY - Sumarni Sumarni; Warni Fridayanti; Tri Wahyuni Akademi Kebidanan YLPP Purwokerto (Jurnal Kebidanan, 2013)
THE DIFFERENCES IN NUTRITIONAL STATUS OF CHILDREN OF WORKING MOTHERS WITH AREN’T WORKING IN THE KEJOBONG DISTRICT PURBALINGGA REGENCY Sumarni, Warni Fridayanti & Tri Wahyuni Akademi Kebidanan YLPP Purwokerto ABSTRACT The infancy is a vulnerable time for nutritional problems. At this time, children experience rapid growth and development and this require nutritious food. Nutritional adequacy can be influenced by the mother's occupation. Mothers work closely relation to earned income mothers to buy nutritious food, so the nutritional intake can be maintained and toddlers are not malnourished. To knowing the differences in nutritional status of children of working mothers with children under five who are not working in the district Kejobong Purbalingga. This research is a observational with cross sectional approach. The sample was all children under five in sub Kejobong mother Purbalingga as many as 97 people. Analysis using percentage distributions and U Mann Whitney test. Nutritional status of children of mothers who work most toddler in the category of less that 26 people (45.6%). Nutritional status of children of mothers who did not work most toddler much in both categories with 26 people (66.7%). There are differences in nutritional status of children of working mothers with children under five who are not working in the district Kejobong Purbalingga (p = 0.009). There was a differences in nutritional status of children of working mothers with children under five who are not working in the district Kejobong Purbalingga. Both mothers toddlers who work and who do not work should pay more attention to the needs of children by providing nutritious foods. Keywords : Nutritional status, working mother